Collection of homozygous mutant mouse embryonic stem cells arising from autodiploidization during haploid gene trap mutagenesis. Issue 10 (15th March 2018) - Yamanishi, Ayako; Matsuba, Atsushi; Kondo, Ryohei; Akamatsu, Rie; Tanaka, Sachiyo; Tokunaga, Masahiro; Horie, Kyoji; Kokubu, Chikara; Ishida, Yasumasa; Takeda, Junji
Abstract: Haploid mouse embryonic stem cells (ESCs), in which a single hit mutation is sufficient to produce loss-of-function phenotypes, have provided a powerful tool for forward genetic screening. This strategy, however, can be hampered by undesired autodiploidization of haploid ESCs. To overcome this obstacle, we designed a new methodology that facilitates enrichment of homozygous mutant ESC clones arising from autodiploidization during haploid gene trap mutagenesis. Haploid mouse ESCs were purified by fluorescence-activated cell sorting to maintain their haploid property and then transfected with the Tol2 transposon-based biallelically polyA-trapping (BPATrap) vector that carries an invertible G418 plus puromycin double selection cassette. G418 plus puromycin double selection enriched biallelic mutant clones that had undergone autodiploidization following a single vector insertion into the haploid genome. Using this method, we successfully generated 222 homozygous mutant ESCs from 2208 clones by excluding heterozygous ESCs and ESCs with multiple vector insertions. This relatively low efficiency of generating homozygous mutant ESCs was partially overcome by cell sorting of haploid ESCs after Tol2 BPATrap transfection. These results demonstrate the feasibility of our approach to provide an efficient platform for mutagenesis of ESCs and functional analysis of the mammalian genome.